Neuronex: An Immersive Learning Experience Using Augmented Reality - Dangol, Rejina; Shrestha, Shreeyansi; Thakur, Sneha; Daha, Wagmi; Amatya, Kunjan (KEC Journal of Science and Engineering, 2026)
Augmented Reality (AR) technology has emerged as a powerful tool in education, offering immersive and interactive learning experiences. This study presents Neuron-X, an e-learning application designed to bridge the gap between traditional instructional methods and modern, technology-enhanced education. The application integrates 3D models created in Blender with AR functionalities developed in Unity to visualize and interact with digital content in real-world contexts. Through interactive 3D models, diagrams, and simulations, Neuron-X aims to simplify complex concepts, promote active engagement, and improve knowledge retention among middle school students. The system’s flexibility allows it to be applied across multiple subject areas, making it suitable for both educators and learners. By incorporating AR into the learning process, this research seeks to enhance student engagement, support diverse learning needs, and demonstrate the potential of AR-based tools in improving academic performance.